Structurally Colored Radiative Cooling Cellulosic Films. Issue 26 (17th July 2022) - Zhu, Wenkai; Droguet, Benjamin; Shen, Qingchen; Zhang, Yun; Parton, Thomas G.; Shan, Xiwei; Parker, Richard M.; De Volder, Michael F. L.; Deng, Tao; Vignolini, Silvia; Li, Tian
Abstract: Daytime radiative cooling (DRC) materials offer a sustainable approach to thermal management by exploiting net positive heat transfer to deep space. While such materials typically have a white or mirror‐like appearance to maximize solar reflection, extending the palette of available colors is required to promote their real‐world utilization. However, the incorporation of conventional absorption‐based colorants inevitably leads to solar heating, which counteracts any radiative cooling effect. In this work, efficient sub‐ambient DRC (Day: −4 °C, Night: −11 °C) from a vibrant, structurally colored film prepared from naturally derived cellulose nanocrystals (CNCs), is instead demonstrated. Arising from the underlying photonic nanostructure, the film selectively reflects visible light resulting in intense, fade‐resistant coloration, while maintaining a low solar absorption (≈3%). Additionally, a high emission within the mid‐infrared atmospheric window (>90%) allows for significant radiative heat loss. By coating such CNC films onto a highly scattering, porous ethylcellulose (EC) base layer, any sunlight that penetrates the CNC layer is backscattered by the EC layer below, achieving broadband solar reflection and vibrant structural color simultaneously. Finally, scalable manufacturing using a commercially relevant roll‐to‐roll process validates the potential to produce such colored radiative cooling materials at a large scale from a low‐cost and sustainable feedstock. Abstract : Structurally colored films capable of full‐time sub‐ambient radiative cooling are prepared from a composite of cellulose nanocrystals and ethylcellulose. The distinct nanostructure within each layer allows for selective reflection of visible light generating color, whilst maintaining a broadband solar reflection. Finally, by demonstrating roll‐to‐roll fabrication, the potential for commercial production from this low‐cost and sustainable feedstock is substantiated.